Improving effectiveness of glaucoma screening during prophylactic medical examinations: current approaches - M.A. Kazanfarova; I.B. Alekseev; A.L. Lindenbraten; S.A. Kochergin (РМЖ "Клиническая офтальмология", 2019)
M.A. Kazanfarova1,2, I.B. Alekseev1, A.L. Lindenbraten3, S.A. Kochergin1 1Russian Medical Academy of Continuous Professional Education,  Moscow, Russian Federation 2The International Medical Cluster Foundation, Moscow, Russian Federation 3N.A. Semashko National Research Institute of Public Health, Moscow, Russian Federation Background: early diagnosis of diseases in clinically healthy persons is the basis of prophylactic medical examinations. In addition to cardiovascular disorders, cancer, diabetes, and chronic lung diseases, glaucoma is one of the major causes of disability in Russian Federation. Prophylactic medical examinations for glaucoma are less addressed in domestic published data than for other diseases which results in disability and early death. Aim: to assess the effectiveness of screening for glaucoma in Russian Federation, to uncover ineffective areas, and to suggest potential solutions. Materials and Methods: the 35-item questionnaire for ophthalmologists who provide primary ocular care was developed (screening questions are addressed below). Survey responses from 126 ophthalmologists who provide primary ocular care were anonymous. Results: 37% of respondents consider prophylactic medical examinations effective while 63% consider prophylactic medical examinations ineffective. Currently, glaucoma is diagnosed more often at early stages, i.e., 34% of respondents diagnose glaucoma at early stage, 60% at early-to-moderate stage, and 6% at moderate-to-advanced stage. 71% of respondents diagnose glaucoma in patients who visit an ophthalmologist independently, 29% diagnose glaucoma in the course of prophylactic medical examinations. 46% of respondents report that IOP measurements during prophylactic medical examinations in adults result in more often diagnosis of glaucoma at early stages. 26% diagnose glaucoma more often but at later stages while 28% do  not diagnose glaucoma more often. Conclusions: currently, glaucoma is diagnosed more often at early stages but mainly in patients who visit an ophthalmologist independently. This is the result either of poor coverage of the population by prophylactic medical examinations or their poor quality. Revision of fundamental approach to glaucoma screening is required, i.e., switch from mass screening using tonometry (which is characterized by high percentage of errors) to target screening using advanced diagnostic tools. Keywords: prophylactic medical examinations, screening, medical prevention, chronic noninfectious disorders, glaucoma, risk factors, early stage. For citation: Kazanfarova M.A., Alekseev I.B., Lindenbraten A.L., Kochergin S.A. Improving effectiveness of glaucoma screening during prophylactic medical examinations: current approaches. Russian Journal of Clinical Ophthalmology. 2019;19(3):122–127. About the authors: 1,2Marina A. Kazanfarova — MD, postgraduate student, Project Manager of the International Medical Cluster Foundation, ORCID iD 0000-0001-7401-9538; 1Igor B. Alekseev — MD, PhD, Professor, ORCID iD 0000-0002-4506-4986; 3Aleksandr L. Lindenbraten — MD, PhD, Professor, ORCID iD 0000-0003-3335-7893; 1Sergey A. Kochergin — MD, PhD, Professor, ORCID iD 0000-0002-8913-822X. 1Russian Medical Academy of Continuous Professional Education. 2/1, Barrikadnaya str., Moscow, 125993, Russian Federation. 2 The International Medical Cluster Foundation. 35–1, Usachev str., Moscow, 119048, Russian Federation. 3N.A. Semashko National Research Institute of Public Health. 12–1, Vorontsovo Pole str., Moscow, 105064, Russian Federation. Contact information: Marina A. Kazanfarova, e-mail: a.m.aliverdieva@gmail.com. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 15.04.2019.